2018
DOI: 10.1590/1678-4324-2018160489
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of Thermal Inactivation of β-Galactosidase from Aspergillus oryzae

Abstract: For optimization of biochemical processes in food and pharmaceutical industries, the evaluation of enzyme inactivation kinetic models is necessary to allow their adequate use. Kinetic studies of thermal inactivation of βgalactosidase from Aspergillus oryzae were conducted in order to critically evaluate mathematical equations presented in the literature. Statistical analysis showed that Weibull model presented the best adequacy to residual enzymatic activity data through the processing time and its kinetic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…The degree and/or intensity of the thermal disruption of the noncovalent linkages in enzymes can be predicted through analysis of the enthalpy parameter, ΔH # [ 62 , 71 ]. It can be seen from Table 4 that while ΔG # increased with increasing temperature, ΔH # , like ΔS # , remained unchanged for each lipase.…”
Section: Resultsmentioning
confidence: 99%
“…The degree and/or intensity of the thermal disruption of the noncovalent linkages in enzymes can be predicted through analysis of the enthalpy parameter, ΔH # [ 62 , 71 ]. It can be seen from Table 4 that while ΔG # increased with increasing temperature, ΔH # , like ΔS # , remained unchanged for each lipase.…”
Section: Resultsmentioning
confidence: 99%
“…The plots of residual activity vs. incubation time for the enzyme were linear, with R 2 > 81%, which indicated that the inactivation could be expressed in terms of first-order kinetics in the temperature range of 50–65 °C. The kinetic enzymatic modeling of thermal inactivation and the determination of its thermodynamic parameters were analyzed at changeable temperatures and various conditions by [ 66 ]. The determinations of half-life (t 1/2 ) are more accurate and reliable especially when computing the stability properties of an enzyme at different temperatures [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3D plot with a determination coefficient of R 2 = 0.977 is shown in Figure 2. As already mentioned (Klein et al, 2018), this representation is an innovative approach in the field of thermal inactivation of enzymes, offering the possibility to evaluate the interaction of time and temperature on enzyme activity. For a better analyze of the thermal stability of Rpbgal, EM parameters are used to plot activity versus time (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the possibilities that Rpbgal could offer in food processing industries from the thermal properties point of view, it is compared to a commercial βgalactosidase from Aspergillus oryzae. Recently, the thermal inactivation of this enzyme (CAS Number: 9031-11-2) was studied by Klein et al (2018) in the temperature range 331 -339 K using oNPG as substrate in an acidic buffer. The temperature dependence of tR obtained for Rpbgal is compared with that of the commercial βgalactosidase in Figure 4.…”
Section: Resultsmentioning
confidence: 99%